Clinical trial perceptions and knowledge: the results of three surveys administered to U.S. physicians, surgeons, nurses, clinic administrators and clinical research industry professionals - Kopjar, Veljko (International Journal of Clinical Trials, 2022)
Background: Surveys were administered to clinicians and non-clinicians on various clinical trial-related topics including their understanding of FDA medical device terminology, investigator-initiated trials (IITs), the level of institutional support for clinical trials at their respective sites and the use of wearable technologies in collecting trial data. Methods: Three online surveys were, collectively, administered to over 350 respondents in the United States using an online tool. Results: The surveys found that the majority of the surveyed clinicians and clinical research professionals do not know the difference between FDA-approved and FDA-cleared devices, awareness of IITs and institutional support for clinical trials varies by medical specialty, and there are noteworthy differences between orthopedic surgeons and oncologists as to whether wearable technologies should be used to collect trial data. Conclusions: The study concluded that there are many physicians and surgeons who cannot accurately distinguish between FDA-approved and FDA-cleared devices, yet they claim to know the difference. It was also observed that oncology centers are more likely to be supportive of clinical trials, as reported by clinicians, as compared to orthopedic centers. Less than half of the surveyed oncology respondents are supportive of the use of wearable technologies in a clinical trial setting-whereas more than half of the orthopedic respondents are supportive of the same. The study also found that most of the surveyed oncologists are familiar with IITs whereas most of the orthopedic surgeons are not familiar with IITs.